Do An(iii) and Ln(iii) ions form heteroleptic complexes with diglycolamide and hydrophilic BT(B)P ligands in solvent extraction systems? A spectroscopic and DFT study. (3rd April 2019) - Herdzik-Koniecko, Irena; Wagner, Christoph; Trumm, Michael; Müllich, Udo; Schimmelpfennig, Bernd; Narbutt, Jerzy; Geist, Andreas; Panak, Petra J.
Abstract : Formation of heteroleptic complexes would explain a discrepancy between results from solvent extraction and from spectroscopy reported earlier. Abstract : Time-Resolved Laser Fluorescence Spectroscopy (TRLFS) was used to study the complexation of Cm(iii ) and Eu(iii ) in solvent extraction systems consisting of an organic phase containing TODGA (tetra- n -octyl diglycolamide) as an extracting agent and an aqueous phase containing hydrophilic complexing agents, tetrasodium salts of 2, 6-bis(5, 6-di(3-sulphophenyl)-1, 2, 4-triazin-3-yl)pyridine, SO3 -Ph-BTP 4−, or 6, 6′-bis(5, 6-di(3-sulphophenyl)-1, 2, 4-triazin-3-yl)-2, 2′-bipyridine, SO3 -Ph-BTBP 4− . Only one complex, homoleptic [Cm(TODGA)3 ](NO3 )3, was found in the organic phase. No heteroleptic complexes of Cm(iii ) with TODGA and SO3 -Ph-BTP 4− have been detected. In contrast, in dilute aqueous HClO4 solutions containing TEDGA (a hydrophilic homologue of TODGA) and SO3 -Ph-BTP 4− ligands, seven different Cm(iii ) species were identified by their distinct emission spectra. Apart from the emission bands corresponding to the hydrated Cm 3+ cation and to the complexes [Cm(SO3 -Ph-BTP)] − and [Cm(TEDGA) n ] 3+ ( n = 1–3), two further emission bands were ascribed to heteroleptic complexes [Cm(TEDGA)(SO3 -Ph-BTP)] − and [Cm(TEDGA)2 (SO3 -Ph-BTP)] − . In a similar aqueous solution containing TEDGA and SO3 -Ph-BTBP 4−, only one heteroleptic complex was identified, [Cm(TEDGA)(SO3 -Ph-BTBP)] − . In addition, quantum chemical optimisation of the structures of the postulated heteroleptic complexes was performed.